Exploration of a new hepatitis a surveillance system in Beijing, China: based on molecular epidemiology - Huai Wang; Weixin Chen; Wenting Zhou; Feng Qiu; Wenjiao Yin; Jingyuan Cao; Pei Gao; Qianli Yuan; Min Lv; Shuang Bai; Jiang Wu (BMC Infectious Diseases, 2022)
Abstract Background The incidence of hepatitis A virus (HAV) infection is low in Beijing, China, but the risk of outbreaks still exists. It is difficult to identify possible sources of infection among sporadic cases based on a routine surveillance system. Therefore, a more effective surveillance system needs to be established. Methods The epidemiological data of hepatitis A were obtained from a routine surveillance system. Patients with HAV confirmed at the local hospitals were asked to complete a questionnaire that included additional case information and possible sources of infection. Serum and fecal specimens were also collected for testing HAV RNA by polymerase chain reaction. In addition, the 321-nucleotide segment of the VP1/2A junction region was sequenced to determine the HAV genotype. Results In 2019, 110 HAV cases were reported in Beijing, with an incidence rate of 0.51/100,000. 61(55.5%) of these patients were male. The greatest proportion of these patients were aged from 30 to 60 years. The rate was lower in suburban and rural areas compared to urban areas. Contaminated food consumption, particularly seafood consumption, was the primary potential source of infection. Among the 16 specimens of confirmed HAV cases that could be sequenced, 93.8% were HAV IA, and 6.3% were HAV IB. In addition, the samples collected from all HAV sequences in this investigation showed 89.4–100% nucleotide homology. Two groups (each with three sporadic cases) showed 100% nucleotide homology. The three sporadic cases in one group had the same possible source of infection: contaminated salad with raw vegetables and seafood. In the other group, the three sporadic cases did not have an epidemiological connection. Conclusions In a low HAV prevalent area, such as in Beijing, incorporating molecular epidemiology into the routine surveillance system could help inform possible clusters of outbreaks and provide support for earlier control of HAV transmission. Nevertheless, increased sampling from detected cases and improved specimen quality are needed to implement such a system.